In situ high-speed synchrotron X-ray imaging of laser-based directed energy deposition of the alloying process with dissimilar powders. (March 2022) - Wang, Hui; Gould, Benjamin; Haddad, Marwan; Moorehead, Michael; Couet, Adrien; Wolff, Sarah J.
Abstract: Laser-based directed energy deposition (DED) additive manufacturing (AM) of the alloying process is performed using mixtures of Mo, Nb, Ti, and V powders and directly observed through in situ high-speed synchrotron X-ray imaging. The investigation on the integration of dissimilar powders into a single melt pool will narrow the gaps between the applied research and the fundamental understanding of the impact of different elemental powders on melt pool properties and defect production in the alloying formation via DED AM. The different traveling trajectories of four types of powders are revealed, such as the trajectories of most Mo powders on the top surface of the melt pool and the trajectories of Nb powders along with the melt flow. The melting modes, melting times, and the size changes of these four-element powders during the alloying process are obtained. Ti powders melt the fastest among these four powders. Ti and V powders melt near the site where they are delivered to the melt pool, while Mo and Nb powders melt when traveling with melt flow. The dynamics and velocities of melt flow in different sections of the melt pool are revealed, and the velocities and fluctuations near the area of the laser beam with the range from 0.134 m/s to 0.849 m/s are the largest in melt pool flow. The melt flow will benefit the uniform element distributions in the fabricated alloy. This study will provide a fundamental understanding of alloying formation via DED AM processes. Highlights: MoNbTiV was in situ alloyed by laser DED AM with elemental powders. The alloying process was directly observed by high-speed synchrotron X-ray imaging. The driving forces of buoyancy, drag force, Marangoni flow, and hydraulic pressure in the melt pool were analyzed. The dynamics of melt-pool flow during the DED alloying process were discussed. The motion, melting modes, and melting times of four powders were revealed with of Mo behaving in contrast to the other materials.